Tadalafil 복용 후 발생한 중심장액맥락망막병증 1예 - 윤요셉(Yo Sep Yoon), 이승환(Seung hwan Lee), 우제문(Je Moon Woo), 민정기(Jung Kee Min) (Daihan angwa haghoi jabji, 2018)
목적: 기저질환 및 기타 약물 복용이 없는 환자에서 2개월간 Tadalafil (Cialis®) 복용 후 발생한 중심장액맥락망막병증의 증례를 보고하고자 한다. 증례요약: 49세 남자 환자로 내원 10일 전부터 시작된 우안의 갑작스런 변시증과 시력저하 증상으로 본원에 전원되었다. 내원 당시 시행한 시력검사상 교정시력 우안 6/20 좌안 18/20으로 측정되었으며, 안저 검사 소견상 우안 위쪽, 아래쪽 혈관 아케이드 사이에서 큰 장액성 망막박리 소견이 관찰되었다. 병력상 기왕력은 확인되지 않았지만, 2개월 전부터 일주일에 3회 정도 Tadalafil을 복용하였다. 이후 Tadalafil 복용을 중단하고 보존적 치료 및 경과 관찰하였으며, 2개월 후 망막하액은 소실되었고 교정시력도 우안 20/20으로 회복되었다. 결론: Tadalafil은 phosphodiesterase (PDE)-5 억제제로서 발기부전 치료제로 주로 처방된다. PDE-5 억제제는 망막 및 맥락막 혈관확장 및 혈류의 저해를 유발하여 중심장액맥락망막병증을 일으킬 수 있다. 이번 증례를 통하여 중심장액맥락망막병증 환자를 접할 때는 철저한 병력청취를 통하여 놓치기 쉬운 약물까지도 파악해야 하고 원인이 되는 약물을 중단시켜야 함을 확인할 수 있었다. Purpose: To describe a patient who presented with central serous chorioretinopathy after 2 months of tadalafil administration without any other underlying disease or medication. Case summary: A 49-year-old male patient was transferred from a local clinic with metamorphopsia and decreased visual acuity in the right eye. His visual acuity was 6/20 in the right eye and 18/20 in the left eye. The fundus examination showed a large serous detachment between the superior and inferior blood vessel arcades in the right retina. In his medical history, he used tadalafil three times a week for 2 months. His medication was then stopped, and a follow-up examination was scheduled. After 2 months, a fundus examination showed resolution of the subretinal fluid, and his corrected visual acuity recovered to 20/20. Conclusions: Tadalafil (Cialis®) is a phosphodiesterase (PDE)-5 inhibitor and predominantly prescribed for the treatment of erectile dysfunction. PDE‐5 inhibitors may be potent vasodilators in the retina and choroid, and may induce choroidal vessel engorgement leading to leakage across the retinal pigment epithelium and accumulation of subretinal fluid in selected patients. When making a diagnosis as central serous chorioretinopathy, the physician should confirm the causative drugs that are easy to miss, by performing a thorough review of the patient’s medical history and promptly terminating the causative drugs. KCI Citation Count: 0